Renovascular Hypertension due to a Paradoxical Reaction in an Immunocompetent Patient: A Clinical Case Report - Ghiletchi, Angela; Coelho, Carolina; Ferreira, Inês; Fiúza M. Rua, Inês; Cabaço, Sérgio; Bernardino, Rita; Nazário Leão, Rodrigo (International Journal of Innovative Research in Medical Science, 2024)
Renovascular hypertension (RVH), resulting from arterial narrowing that compromises renal blood flow, poses significant clinical challenges due to its association with severe complications like refractory hypertension and renal insufficiency. This case report documents a 27-year-old immunocompetent woman who developed RVH and Posterior Reversible Encephalopathy Syndrome (PRES) as a paradoxical reaction to anti-tuberculous therapy (ATT) for disseminated tuberculosis (TB). Despite standard ATT, the patient exhibited persistent hypertension and neurological symptoms, including headache. Imaging revealed necrotic lymph nodes compressing the right renal artery, leading to RVH, and MRI confirmed PRES. Management involved high-dose corticosteroids to mitigate the inflammatory response, resulting in symptom resolution and normalization of blood pressure over an 18-month period. This case underscores the need for a multidisciplinary approach in managing complex interactions between TB treatment, paradoxical reactions, and hypertensive complications, even in immunocompetent patients. The report highlights the importance of vigilant monitoring and timely intervention to prevent long-term complications, emphasizing the unpredictable nature of TB and its treatment outcomes.